New fragmentations and new cooperations in the Turkish bourgeoisie - ÇOKGEZEN, MURAT (PION LTD, 2000)
The establishment of a new business association constitutes both a fragmentation and a cooperation among capitalists. The author aims to determine the causes of the fragmentation and the cooperation by discussing the background of new business associations being established in Turkey: it is concluded that conflicting interests of capitalists are a major source of those two phenomena. It is also found that both heterogeneity and homogeneity within the cooperating group may facilitate cooperation. Fragmenting aspects of heterogeneity are associated with selective incentives.
Keywords: EMPLOYERS